2021
DOI: 10.1016/j.jmig.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Novel Technology to Capture Objective Data from Patients’ Recovery from Laparoscopic Endometriosis Surgery

Abstract: Study Objective: To assess the feasibility of a noncontact radio sensor as an objective measurement tool to study postoperative recovery from endometriosis surgery. Design: Prospective cohort pilot study. Setting: Center for minimally invasive gynecologic surgery at an academically affiliated community hospital in conjunction with in-home monitoring. Patients: Patients aged above 18 years who sleep independently and were scheduled to have laparoscopy for the diagnosis and treatment of suspected endometriosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The same radio device was used to detect errors in medication self-administration ( 71 ) and monitor patients with Alzheimer’s disease ( 72 ), endometriosis ( 73 ), COVID-19 ( 74 ), and facioscapulohumeral muscular dystrophy (FSHD) ( 75 ). Also, we have explored the use of the device with individuals with PD in a small pilot study focused on sleep and daily activities ( 76 ).…”
Section: Methodsmentioning
confidence: 99%
“…The same radio device was used to detect errors in medication self-administration ( 71 ) and monitor patients with Alzheimer’s disease ( 72 ), endometriosis ( 73 ), COVID-19 ( 74 ), and facioscapulohumeral muscular dystrophy (FSHD) ( 75 ). Also, we have explored the use of the device with individuals with PD in a small pilot study focused on sleep and daily activities ( 76 ).…”
Section: Methodsmentioning
confidence: 99%
“…This study has also shown that contantless sensors have great potential to revolutionise human vital sign detection and monitoring. The study has demonstrated that contactless sensing technology can be used to limit contact between patients, [37] Surgery recovery (endometriosis) FMCW Not specified [38] Head position FMCW Not specified BodyCompass [41] Sleep position FMCW 5.4 GHz -7.2 GHz Emirald [39] Pacing FMCW Not specified [42] PD FMCW Not specified [40] Human Figure FMCW 5.46 -7.24 [34] Respiratory rate and heartbeat FMCW 5.8 [35] Respiration rate FMCW 5.8 [17] Human activity (sitting standing) CSI 2.4…”
Section: Lessons Learned and Research Directionmentioning
confidence: 99%
“…According to the authors, results indicate that there is a relationship between time to exit bed and CSS. 13) Authors in [37] also used Emerald to monitor postoperative recovery process for patients recovering from endometriosis surgery. The study was conducted on three women where the device was placed on each of their homes to study the patients movement and sleep for five weeks before surgery and five weeks after surgery.…”
Section: Target Detectionmentioning
confidence: 99%
“…One self-tracking app for recording cannabis use has also been used to explore intervention effects in a subset of participants with endometriosis. 59 Lastly, a small pilot study of patients with endometriosis (N = 3) explored sleep changes before and after laparoscopic surgery using a non-contact sensor installed at home, 60 which may be an alternative way of collecting data from patients and of overcoming barriers with self-reports or the use of digital technologies that might be challenging for some participants to use (e.g., post-operatively).…”
Section: Use Of Digital Technologies In Research On Endometriosismentioning
confidence: 99%